Cascade Nucleophilic Addition/cyclization/C−N Coupling of o‐Iodo‐phenyl Isothiocyanates with Propargylamines: Access to Benzimidazo[2, 1‐b]thiazole Derivatives. Issue 12 (11th October 2021) - Zhong, Xianqiang; He, Feng; Ran, Qiuye; Li, Wenjing; Xiong, Huilan; Zhou, Wei
Abstract: A highly efficient and mild sequential nucleophilic addition/ cyclization/copper catalyzed C−N coupling reaction of o ‐iodophenyl isothiocyanates with propargylamines has been realized, which delivers a variety of benzimidazo[2, 1‐ b ]thiazole derivatives in good yields. Moreover, this protocol could be performed at gram scale and applied to the concise synthesis of tilomisole. Abstract : A highly efficient and mild sequential nucleophilic addition/cyclization/copper catalyzed C−N coupling of o ‐iodophenyl isothiocyanates with propargylamines has been realized, which delivers a variety of benzimidazo[2, 1‐ b ]thiazole and benzimidazo[2, 1‐b]thiazolines derivatives in good yields.